Security initiatives of the Russian Federation, the Republic of Belarus, and the People’s Republic of China: theoretical and practical aspects - Zhuravskaya, Olga S. (Journal of the Belarusian State University. International Relations, 2026)
This article examines changes introduced since 2022 in the strategic and doctrinal documents of the Russian Federation, the Republic of Belarus, and the People’s Republic of China, as well as the practical security initiatives advanced by these states in response to the changing international order and current global situation. The 2023 Foreign policy concept of the Russian Federation introduced new regional categories and revised foreign policy priorities. The 2024 Concept of national security of the Republic of Belarus incorporated new concepts, including «biological security» and «electoral sovereignty». The People’s Republic of China, for its part, has put forward the Global security initiative, which is based on cooperation among states, the rejection of bloc confrontation, and the peaceful coexistence of peoples. The article argues that the foundations of the existing international security system require reassessment, given its limited effectiveness and the extent to which it is increasingly disregarded by many international actors. It also evaluates the security initiatives proposed by the Russian Federation, the Republic of Belarus, and the People’s Republic of China, considering their prospects for implementation and their potential to gain support from other states.
Keywords: Global security initiative; international security; Eurasian charter of diversity and multipolarity in the 21st century; Russian Federation; Republic of Belarus; People’s Republic of China